Success in Indonesia Analyzed Through Price, Quality, Branding, Promotion, and Consumer Perception - Syahlan, Fatra; Ratih Hurriyati, Ratih; Dirgantari, Puspo Dewi (West Science Business and Management, 2023)
The present research delves into the elements that influence the performance of private label businesses in Indonesia's Micro, Small, and Medium-Sized Enterprises (MSMEs) market. Specifically, it examines the interdependent aspects of pricing strategy, brand, promotion, and consumer perception. Structural Equation Modeling (SEM), a quantitative method, was utilized to examine the association between these factors utilizing a sample of 197 MSMEs. The findings provide important information for MSMEs trying to survive in the cutthroat market environment by demonstrating a strong and positive correlation between each component and private label performance. This research provides useful suggestions for enhancing private label tactics and expanding market share in Indonesia.